2019
DOI: 10.1007/s12144-019-00369-9
|View full text |Cite
|
Sign up to set email alerts
|

A lexical approach to laughter classification: Natural language distinguishes six (classes of) formal characteristics

Abstract: Although research on laughter is becoming increasingly common, there is no consensus on the description of its variations. Investigating all verbal attributes that relate to the term laughter may lead to a broad set of descriptors deemed important by the speakers of a language. Through a linguistic corpus analysis using the German language, formal attributes of laughter were identified (original pool: 1148 single-word descriptors and 172 multi-word descriptors). A category system was derived in an iterative pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…In addition to the similar HUMOR IS FORCE metaphor (unbändiges Lachen 'irrepressible laughter') as in English, humor was also conceptualized by internal bodily experience in the German context, which was instantiated in metaphors like HUMOR IS SENSORY PERCEPTIONS (bitter lachen 'laugh bitterly') and HUMOR IS LOCATED IN THE BODY (Mit einem fröhlichen Lachen auf den Lippen 'a merry laugh on her lips'; Alles lachte ja in ihm 'everything in him laughed'). In another vein of the research, Ruch et al (2019) investigated the attributes associated with laughter. In their Study 1, Ruch et al (2019) classified six categories of laughter-related attributes by sorting out all co-occurred terms with the flections of lachen (meaning 'laughter' or 'to laugh') in a number of German corpora.…”
Section: Embodied Metaphor and Humormentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the similar HUMOR IS FORCE metaphor (unbändiges Lachen 'irrepressible laughter') as in English, humor was also conceptualized by internal bodily experience in the German context, which was instantiated in metaphors like HUMOR IS SENSORY PERCEPTIONS (bitter lachen 'laugh bitterly') and HUMOR IS LOCATED IN THE BODY (Mit einem fröhlichen Lachen auf den Lippen 'a merry laugh on her lips'; Alles lachte ja in ihm 'everything in him laughed'). In another vein of the research, Ruch et al (2019) investigated the attributes associated with laughter. In their Study 1, Ruch et al (2019) classified six categories of laughter-related attributes by sorting out all co-occurred terms with the flections of lachen (meaning 'laughter' or 'to laugh') in a number of German corpora.…”
Section: Embodied Metaphor and Humormentioning
confidence: 99%
“…In another vein of the research, Ruch et al (2019) investigated the attributes associated with laughter. In their Study 1, Ruch et al (2019) classified six categories of laughter-related attributes by sorting out all co-occurred terms with the flections of lachen (meaning 'laughter' or 'to laugh') in a number of German corpora. One of the categories of the laughter-related attributes was intensity, containing features such as the degree to which the body is involved in laughing (e.g., bebend, meaning 'quivering'; krampfartig, meaning 'spasmodic').…”
Section: Embodied Metaphor and Humormentioning
confidence: 99%
See 1 more Smart Citation
“…The articulate expression of laughter changes across sex, individuals, and settings 47 as different individuals have their favorite subset of phones for laughing. 48 Ruch et al 49 pointed out that there are biometric traits in laughter like in fingerprints and confirmed that this field has not been exploited. Thus, the aim and major contribution of this study is to investigate the use of laughter signature for GR using audio laughter.…”
Section: Introductionmentioning
confidence: 98%
“…Ruch et al 49 pointed out that there are biometric traits in laughter like in fingerprints and confirmed that this field has not been exploited. Thus, the aim and major contribution of this study is to investigate the use of laughter signature for GR using audio laughter.…”
Section: Introductionmentioning
confidence: 99%